IJABI DAN PENDIDIKAN AHLUL BAIT: STUDI KASUS PADA YAYASAN MUTHAHHARI BANDUNG - Nunu Ahmad An-Nahidl (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The all Indonesian Assembly of Ahlulbayt Association (IJABI) is a Shia Muslim organization model of Indonesia. IJABI have distinctive characteristics. IJABI spread the ideology of Ahlulbayt by giving awards to the plurality and cultural approaches, as well as prioritizing moral glory rather than jurisprudence. This qualitative study will answer the following questions; Is Motahhari Foundation is an educational institution Shia? How does the relationship between IJABI and Motahhari Foundation? Is Motahhari Foundation also runs IJABI mission? Is Motahhari Foundation educates students about the Shia? How about Shia learning is given?